2012
DOI: 10.1371/journal.pone.0033864
|View full text |Cite
|
Sign up to set email alerts
|

Ocular Application of the Kinin B1 Receptor Antagonist LF22-0542 Inhibits Retinal Inflammation and Oxidative Stress in Streptozotocin-Diabetic Rats

Abstract: PurposeKinin B1 receptor (B1R) is upregulated in retina of Streptozotocin (STZ)-diabetic rats and contributes to vasodilation of retinal microvessels and breakdown of the blood-retinal barrier. Systemic treatment with B1R antagonists reversed the increased retinal plasma extravasation in STZ rats. The present study aims at determining whether ocular application of a water soluble B1R antagonist could reverse diabetes-induced retinal inflammation and oxidative stress.MethodsWistar rats were made diabetic with S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
71
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(81 citation statements)
references
References 59 publications
10
71
0
Order By: Relevance
“…The inhibition of increased vascular permeability and edema by SSR240612 is consistent with previous studies using other B1R antagonists in selected peripheral tissues of STZ-diabetic rats. 17,21 Our study, however, is one of the first showing inhibition of LPS-induced vascular permeability and edema by a B1R antagonist as most studies have documented the effects of exogenous B1R agonists on plasma extravasation and the pharmacological characterization of the response with kinin receptors antagonists in LPStreated animals. The inhibition of kinin B1R with SSR240612 reversed hyperglycemia in STZ-diabetic rats.…”
Section: Discussionmentioning
confidence: 89%
“…The inhibition of increased vascular permeability and edema by SSR240612 is consistent with previous studies using other B1R antagonists in selected peripheral tissues of STZ-diabetic rats. 17,21 Our study, however, is one of the first showing inhibition of LPS-induced vascular permeability and edema by a B1R antagonist as most studies have documented the effects of exogenous B1R agonists on plasma extravasation and the pharmacological characterization of the response with kinin receptors antagonists in LPStreated animals. The inhibition of kinin B1R with SSR240612 reversed hyperglycemia in STZ-diabetic rats.…”
Section: Discussionmentioning
confidence: 89%
“…In addition, liraglutide was able to prevent the diabetes-induced increase of caspase-8 and the Bax (proapoptotic)/Bcl-xL (antiapoptotic) ratio. In addition, we found that liraglutide (systemically and topically administered) was able to prevent the diabetes-induced retinal activation of p53, a factor that participates in hypoxic and oxidative stress-mediated retinal cell death (38), as well as several key molecules involved in retinal apoptosis and inflammation such as FasL and iNOS (39)(40)(41).…”
Section: Discussionmentioning
confidence: 93%
“…Rats were then perfused with 30 mL 4% paraformaldehyde followed by 25 mL 1% Albumin in PBS. 19 Retinas were mounted on a glass slide and imaged using a fluorescence microscope (Olympus FSX100; Olympus, Center Valley, PA). Adherent leukocytes were counted in the upper retinal plane closest to the inner limiting membrane.…”
Section: Rvp Measurement By Fluorescein Leakagementioning
confidence: 99%